Astigmatism correction with toric intraocular lenses: wavefront aberrometry and quality of life. Issue 5 (6th March 2013) - Mencucci, Rita; Giordano, Cristina; Favuzza, Eleonora; Gicquel, Jean-Jacques; Spadea, Leopoldo; Menchini, Ugo
Abstract : Background/aim: To evaluate wavefront aberrations and subjective quality of life after toric intraocular lens (TIOL) implantation. Methods: Three groups of subjects who underwent unilateral cataract surgery with intraocular lens (IOL) implantation were compared: (1) toric group (n=40): corneal astigmatism >1.50 D, implanted with Acrysof toric SN60TT IOL (Alcon Inc, Fort Worth,  Texas, USA); (2) astigmatic SN60AT group (n=40): corneal astigmatism >1.50 D, implanted with Acrysof SN60AT IOL; and (3) control group (n=40): corneal astigmatism <1.00 D, implanted with Acrysof SN60AT IOL. Uncorrected distance visual acuity (UDVA), refraction, lower order astigmatism (Z 2 2, Z −2 2 ), Strehl ratio and the modulation transfer function area ratio were evaluated over a 3 month follow-up period. A standardised quality of life test (National Eye Institute Refractive Error Quality of Life Instrument-42) was distributed to both astigmatic groups 3 months postoperatively. Results: Postoperative UDVA and aberrometric values were significantly better (p<0.001) and mean postoperative spherical equivalent was significantly lower (p<0.05) in the toric and control groups compared with the astigmatic SN60AT group. The toric group had significantly better postoperative quality of life compared with the astigmatic SN60AT group (p<0.05). Conclusions: Acrysof TIOL implantation resulted in better visual, refractive and aberrometric results than SN60AT spherical IOL implantation in astigmatic patients, similar to the control group. The better objective optical and retinal image quality resulted in better subjective quality of life after TIOL implantation.